Languages, Design Methods, and Tools for Electronic System Design Selected Contributions from FDL 2016 (Lecture Notes in Electrical Engineering,, 2018)
This book brings together a selection of the best papers from the nineteenth edition of the Forum on specification and Design Languages Conference (FDL), which took place on September 14-16, 2016, in Bremen, Germany. FDL is a well-established international forum devoted to dissemination of research results, practical experiences and new ideas in the application of specification, design and verification languages to the design, modeling and verification of integrated circuits, complex hardware/software embedded systems, and mixed-technology systems. · Covers analog-mixed signal design techniques; · Includes descriptions of methods for reliable system design as well as fault localization; · Introduces stochastic methods for power modeling; · Covers design techniques for analog and adiabatic circuits.